Late Pleistocene aeolian deposition and human occupation on the eastern edge of the deglacial corridor, northeastern Alberta, Canada. (November 2022) - Woywitka, Robin; Froese, Duane; Lamothe, Michel; Wolfe, Stephen
Abstract: The lower Athabasca River basin in northeastern Alberta contains one of the highest known concentrations of prehistoric archaeological sites in the boreal forests of western Canada. This is due to the combination of readily available sources of lithic raw material stone near a major travel corridor, and extensive archaeological survey conducted in advance of oil sands mining. Typological studies have proposed immediate post-glacial occupations that were contemporaneous with, or immediately followed, the catastrophic glacial Lake Agassiz flood through the area at the end of the Pleistocene. Here, we complement the typology age estimates by using stratigraphic relations and infrared stimulated luminescence (IRSL) dating of aeolian material to determine the age of initial human occupation, and reconstruct the environment encountered by early inhabitants of the region. We find that the first occupations in our study area took place near the Pleistocene-Holocene boundary (ca. 11.3 ± 0.8 ka BP), shortly after catastrophic flooding from Lake Agassiz. The post-flood environment was dominated by cold climatic conditions that supported permafrost, presumably during the late Pleistocene, and underwent significant aeolian deposition. Our results indicate that this area represents a portion of the eastern edge of the deglacial corridor into which plants, animals, and humans dispersed following retreat of the Laurentide Ice Sheet.